WOMEN'S DISCRIMINATION IN SAUDI ARABIA REFLECTED IN CARMEN BIN LADEN'S INSIDE THE KINGDOM MEMOIR (2004): A FEMINIST APPROACH - SURYATININGSIH, NOVA (2011)
The major problem of this study is how is women discrimination in Saudi Arabia reflected in Carmen bin laden Inside The Kingdom. The objective of this study is to analyze the memoir based on its structural elements and to analyze the memoir based on the feminist analysis. In analyzing Inside The Kingdom, the writer uses qualitative method and feminist approach. The data sources consist of primary data and secondary data sources. The primary data source is the memoir Inside The Kingdom itself and the secondary data sources are the other sources related to the analysis such as the author‟s biography, books of literary theory and feminism. The method of the data collection is library research. The technique of data analysis is descriptive analysis. The outcomes of the study show the following conclusions. First, from the structural analysis of the memoir shows that Carmen Bin Laden wants to convey her idea about women‟s discrimination. Second, based on Feminist Approach, the conclusion is that there is women discrimination in Carmen Bin Laden‟s memoir Inside The Kingdom. Saudi Arabia tradition implicitly practiced that women being placed as inferior. The discrimination for women is position, role, right and participation.